The Intergenerational Transmission of Income in Switzerland - A Comparison between Natives and Immigrants - Philipp Bauer (University of Basel, Center of Business and Economics (WWZ), 2006)
This paper analyses the intergenerational income mobility for natives and immigrants in Switzerland. An IV approach based on data from two different data sets is used. As there is no adequate data on fathers, I revert to information from a period that differs from actual fathers' work period. This methodological approach leads to a bias of the resulting intergenerational elasticity. Nevertheless, cross-national comparison of income mobility is still possible. A comparison across subgroups of the Swiss population shows strong differences between Swiss and immigrants. Compared to natives, immigrants are more immobile. Also, substantial heterogeneity is found across different ethnic groups. Using quantile regression, mobility for natives is found to be similar for all income quantiles. Among immigrants, mobility is higher at the lower as well as at the upper end of the income distribution. These patterns differ from previous results from other countries.
Keywords: C23; I30; J61; J62; 330; Income mobility; Intergenerational transmission; Immigrants